Government bonds and credit risk : an assesment of diversification and a safe asset in the euro area - Touvras, Alexandros (2019)
Banks’ exposure to risky government bonds has become one of the main reasons of financial instability in recent years, especially in the euro area. The connected fate of banks and their sovereign government, the insufficient amount of safe assets, the high percentages of non-performing loans, as well as the low level of loans supplied to the economy are some of the main issues that need to be tackled in the financial system today. This paper examines the potential benefits of government bond diversification and the introduction of tranches via a new asset in banks’ balance sheets from five countries in the euro area, Greece, Italy, Spain, Portugal and Germany. Additionally, the application of zero risk-weights and the absence of exposure limits to government bonds in banks’ balance sheets is questioned. With the aid of a simulation technique, the distribution of potential future losses for various compositions of banks’ balance sheets is calculated. Furthermore, the credit risk is measured via the VaR or CVaR method. On the one hand, results indicate that diversification of government bonds, may positively reduce banks’ credit risk and thus, lead to an increase in loans supplied. On the other hand, in more stable financial environments such measures may be counter effective. The introduction of sovereign bond backed securities seems to tackle these issues more effectively. When banks hold the safest tranches of such assets, the reduction of credit risk is more effective in all economies examined, which leads to an increase in loan supply in all five countries. Therefore, this study finds support for the creation of a safe asset, as it is suggested in previous literature, in order to tackle some of the main issues that cause financial instabilities in the euro area.